Introduction to social work & social welfare : - Kirst-Ashman, Karen Kay (Cengage Learning, 2017)
5th Edition helps you understand the issues that social workers address every day. Using a clear and engaging writing style, author Karen K. Kirst-Ashman presents a balanced overview within a unifying theme of critical thinking that will train you to use evaluative skills in your coursework and beyond. In addition, you'll study more efficiently and effectively with accompanying digital resources that provide you with opportunities to complete self-assessments as well as pre- and post-tests for each chapter. Thoughtful case studies throughout the text help to prepare you for your career by showing you what social work practice looks like in different contexts and with different populations.